mts(MN9), a cpc-1 allele involved in a translocation - J. Koch; I. B. Barthelmess (Fungal Genetics Reports, 1988)
Among several amino acid analogue sensitive mutants, D.E.A. Catcheside selected mts(MN1) and mts(MN9) via their 5-methyltryptophan sensitive phenotype (1966, Ph.D thesis, University of Birmingham).